Konsep Metode Amtsal dan Implementasinya dalam Pembelajaran - Ulfah, Maria; Kausari, Ahmad; Cahyadi, Ani; Anwar, Chairul (el Buhuth: Borneo Journal of Islamic Studies, 2022)
The need for various innovations in Islamic religious learning in schools is a necessity that must be carried out to develop the quality of education. One aspect that allows innovation in learning is the use of methods that vary according to the situation and condition of the class. The use of appropriate methods in learning is one of the steps that must be taken in order to achieve learning objectives. The proverbs method can be an alternative in responding to the demands of innovation and variation in the learning process. This study aims to describe the concept of the proverb method and its implementation in learning. This research uses a qualitative approach with a literature study method. Sources of data obtained from various books, books, and journal articles will be analyzed and presented in the form of a description. The results of the research show that the proverb method is a method of simulating something abstract with something more concrete and easy to understand. The Proverbs method also gives and motivates people to act according to the purpose of the parable if it is something the soul likes; on the other hand, it also encourages people not to act like the parable because it is something that is hated by the human conscience.